Dalbergioidin Ameliorates Doxorubicin-Induced Renal Fibrosis by Suppressing the TGF-β Signal Pathway - Xianguo Ren; Yun Bo; Junting Fan; Maosheng Chen; Daliang Xu; Yang Dong; Haowei He; Xianzhi Ren; Rong Qu; Yulian Jin; Weihong Zhao; Changliang Xu (Mediators of Inflammation)
We investigated the effect of Dalbergioidin (DAL), a well-known natural product extracted from Uraria crinita, on doxorubicin- (DXR-) induced renal fibrosis in mice. The mice were pretreated for 7 days with DAL followed by a single injection of DXR (10 mg/kg) via the tail vein. Renal function was analyzed 5 weeks after DXR treatment. DXR caused nephrotoxicity. The symptoms of nephrotic syndrome were greatly improved after DAL treatment. The indices of renal fibrosis, the phosphorylation of Smad3, and the expression of alpha-smooth muscle actin (α-SMA), fibronectin, collagen III (Col III), E-cadherin, TGF-β, and Smad7 in response to DXR were all similarly modified by DAL. The present findings suggest that DAL improved the markers for kidney damage investigated in this model of DXR-induced experimental nephrotoxicity.